Microglia display modest phagocytic capacity for extracellular tau oligomers - Majerova, Petra (BioMed Central, 2014)
BACKGROUND: Abnormal misfolded tau protein is a driving force of neurofibrillary degeneration in Alzheimer’s disease. It has been shown that tau oligomers play a crucial role in the formation of intracellular neurofibrillary tangles. They are intermediates between soluble tau monomers and insoluble tau filaments and are suspected contributors to disease pathogenesis. Oligomeric tau can be released into the extracellular space and spread throughout the brain. This finding opens the question of whether brain macrophages or blood monocytes have the potential to phagocytose extracellular oligomeric tau. METHODS: We have used stable rat primary microglial cells, rat peripheral monocytes-derived macrophages, BV2 microglial and TIB67 macrophage immortalized cell lines that were challenged by tau oligomers prepared by an in vitro aggregation reaction. The efficiency of cells to phagocytose oligomeric protein was evaluated with confocal microscopy. The ability to degrade tau protein was analyzed by immunoblotting. RESULTS: Confocal microscopy analyses showed that macrophages were significantly more efficient in phagocytosing oligomerized tau proteins than microglial cells. In contrast to macrophages, microglia are able to degrade the internalized oligomeric tau only after stimulation with lipopolysaccharide (LPS). CONCLUSIONS: Our data suggests that microglia may not be the principal phagocytic cells able to target extracellular oligomeric tau. We found that peripheral macrophages display a high potency for elimination of oligomeric tau and therefore could play an important role in the modulation of neurofibrillary pathology in Alzheimer’s disease. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12974-014-0161-z) contains supplementary material, which is available to authorized users.